Pediatric pharmacokinetics of the antibiotics in the access and watch groups of the 2019 WHO model list of essential medicines for children: a systematic review. Issue 12 (2nd December 2019) - Rashed, Asia N; Jackson, Charlotte; Gastine, Silke; Hsia, Yingfen; Bielicki, Julia; Standing, Joseph F; Tomlin, Stephen; Sharland, Mike
ABSTRACT: Introduction : Pharmacokinetic-pharmacodynamic (PK-PD) studies of antibiotics in pediatrics are limited. Pediatric dosing regimens for many antimicrobial drugs have been historically derived from adult pharmacokinetic data. Most pediatric formularies and dosing guidelines globally are expert-based and provide no rationale for the recommended doses, leading to heterogeneous guidance. Areas covered : We systematically reviewed the current dosing for 28 antibiotics listed in the Access and Watch groups of the 2019 World Health Organization (WHO) Essential Medicines List for children (EMLc). PubMed and EMBASE were searched for all PK-PD and pharmacological studies in pediatrics up to May 2018. In total, 262 pediatric related articles were deemed eligible. The most studied drugs were those where therapeutic drug monitoring is routine (aminoglycosides, glycopeptides) and study reporting detail was variable, with only 60.0% using the PK-PD results in make dosing recommendations. Based on this evidence, dose recommendations for each antibiotic were made. Expert opinion : We provide an up-to-date review of the limited available evidence on pediatric dosing for the 28 commonly prescribed antibiotics in the 2019 WHO EMLc. We propose synthesized dosing recommendations for those antibiotics administered systemically for the treatment of serious infections. Further PK-PD studies in children, particularly with underlying conditions, are needed.